Congenital Hypofibrinogenemia in a Neonate with a Novel Mutation in the FGB Gene - Jun Shinozuka; Nobuo Okumura; Mayumi Nagasawa; Motokazu Nishikado; Sayaka Kadowaki; Itsuro Katsuda; Shinsaku Imashuku (MDPI AG, 2021)
Detection of severe hypofibrinogenemia (<50 mg/dL) in a neonate soon after birth is alarming because of the risk of hemorrhage. A female neonate was noted to be hypofibrinogenemic (<50 mg/dL) on day 0 of birth; she showed no thrombocytopenia/coagulopathy or hemorrhagic symptoms. Considering the possibility of afibrinogenemia, which may cause bleeding, fresh frozen plasma (FFP) was initiated twice a week to maintain her plasma fibrinogen level at 50-100 mg/dL. Thereafter, we found hypofibrinogenemia in her father and elder sister and plasma fibrinogen levels, determined by clot formation and immunological methods, showed similarly reduced values in both the neonate (proband) and her father. Based on a presumed diagnosis of congenital hypofibrinogenemia, sequencing of the fibrinogen genes was performed, revealing a novel heterozygous mutation of FGB (Genbank NG008833); a p.403Try>Stop. The neonate was treated with repeat FFP infusions until two months of age, when treatment was stopped because she remained asymptomatic.